2009
DOI: 10.4103/0974-620x.57310
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of fungal keratitis in urban population of West Bengal, India

Abstract: BackgroundCorneal diseases are one of the major causes of visual loss and blindness, second only to cataract. Amongst corneal diseases, microbial keratitis is a major blinding disease. In some countries, fungal keratitis accounts for almost 50% of patients with culture-proven microbial keratitis.AimThis study was conducted to determine the epidemiological characteristics of fungal keratitis in an urban population of West Bengal and identify the specific pathogenic organisms.MethodsThe charts of patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 15 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…Certain conditions like trauma to the eyeball and therapy with antibiotics and corticosteroids render the eye susceptible to infection with various fungi especially in tropical parts of the world [1]. A large number of studies from India have reported epidemiological and microbiological profile of fungal keratitis [1-8], however, there are only few that have provided a comprehensive analysis of the clinical and laboratory profile [5,7]. Minor differences in the frequency and spectrum of fungi associated with mycotic keratitis have been reported from southern (36.7%) [2] northern (7.3%) [4] western (36.3%) [6] and north-eastern (25.6%) [7] India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain conditions like trauma to the eyeball and therapy with antibiotics and corticosteroids render the eye susceptible to infection with various fungi especially in tropical parts of the world [1]. A large number of studies from India have reported epidemiological and microbiological profile of fungal keratitis [1-8], however, there are only few that have provided a comprehensive analysis of the clinical and laboratory profile [5,7]. Minor differences in the frequency and spectrum of fungi associated with mycotic keratitis have been reported from southern (36.7%) [2] northern (7.3%) [4] western (36.3%) [6] and north-eastern (25.6%) [7] India.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies from India have reported epidemiological and microbiological profile of fungal keratitis [1-8], however, there are only few that have provided a comprehensive analysis of the clinical and laboratory profile [5,7]. Minor differences in the frequency and spectrum of fungi associated with mycotic keratitis have been reported from southern (36.7%) [2] northern (7.3%) [4] western (36.3%) [6] and north-eastern (25.6%) [7] India. Both the studies from northeastern India have reported high prevalence (38% and 42%) of fungal keratitis in the region [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies (15,17) demonstrated a prevalence in males between 50–60 years of age. Khater et al (12) also observed that mycotic keratitis was most prevalent in the 40–60 years age group (52.4% of cases) (12).…”
Section: Discussionmentioning
confidence: 99%
“…MK is a sight-threatening process, corneal infections progress rapidly, inducing epithelial defects and permanent ocular surface damage; Thus a prompt diagnosis of the causative agent is required to administer opportune treatments [1,2,3,4,5,6,7]. In animal models of MK, the immunological response is central to controlling infectious diseases of the eye and is related to the immunological mechanism of the corneal injury [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization and Vision 2020 have recognized that corneal diseases are the second leading cause of blindness after cataract and a major cause of preventable blindness in the developing world [1,2]. Many studies have emphasized the importance of determining the epidemiological profile and performing microbial identification with regard to describing the predisposing factors to develop microbial keratitis (MK) [3,4,5,6]. Factors such as trauma, contact lens wear, dry eye, ocular surface disorders and immunosuppression may alter the immune defense mechanisms of the outer eye, and permit microorganisms to invade the cornea [7].…”
Section: Introductionmentioning
confidence: 99%